Lietuvos istorijos periodizacijos modeliai socialinės istorijos požiūriu - Bumblauskas, Alfredas (Lietuvos istorijos studijos, 2006)
The article reviews periodization models of Lithuanian history that are based on the history of politics and culture. A discussion about the periodization of the history of Lithuania is also renewed, and the insights into periodization that are considered to be up-and-coming are given in the article. In the 20th-century historiography of Lithuania, such insights are found in the works of famous historians Z. Ivinskis, J. Jurginis, and E. Gudavičius. Realizing the limitations of the history of politics and culture, attempts are made to formulate the appropriate assumptions for the creation of a periodization model of the development of Lithuanian society on the basis of the insights of the historians mentioned above and on certain theoretical principles of creation of periodization models related to the integral social German history. Such concepts, related to the political, cultural, and social history, as the Middle Ages, the Early New Ages, the Renaissance, Baroque, and the Age of Enlightenment are under discussion in the article, and the optimal approach to the periodization of the Early History of Lithuania (1009-1795) from the point of view of the history of society is being searched for. The article deals with the question of what is peculiar about the problems of periodization from the point of view of social history. Questions and arguments concerning the beginning of the Early New Ages in the history of Lithuania and the attitude towards Baroque as the civilization epoch of Lithuanian history help to ground the tripartite periodization of the Early History of Lithuania (1009-1795): the epoch of Paganism (1009-1387), the epoch of Europeanization (1387-1569), and the epoch of Baroque. Arguments of political, cultural, and economic development are regarded as basic in the article, and the development of Lithuanian society is viewed as an integral part of this periodization.